2010
DOI: 10.1016/s2255-4971(15)30428-6
|View full text |Cite
|
Sign up to set email alerts
|

Complications of the Screw/Washer Tibial Fixation Technique for Knee Ligament Reconstruction

Abstract: To evaluate the presence of pain at the site of the surgical incision and the need to remove the tibial fixation screw in anterior cruciate ligament (ACL) reconstruction, in relation to sex and body mass index (BMI). Methods: A group of 265 patients who underwent ACL reconstruction with ipsilateral flexor tendon grafts from the thigh in which the tibial fixation technique consisted of using a cortical screw and metal washer, between July 2000 and November 2007, were evaluated. Results: 176 patients were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…To prevent knee stiffness, inflammation control and early knee motion are generally advised [ 38 ]. Postoperative knee pain and function impairment can also be due to hardware intolerance [ 39 ]. In the present systematic review, a total of 26 cases (15.2%) required a second surgical procedure to remove fixation hardware.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent knee stiffness, inflammation control and early knee motion are generally advised [ 38 ]. Postoperative knee pain and function impairment can also be due to hardware intolerance [ 39 ]. In the present systematic review, a total of 26 cases (15.2%) required a second surgical procedure to remove fixation hardware.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Almeida et al they demonstrated a 10.8% rate of hardware removal in patients who had a screw and washer construct on the tibial side for fixation. 39 Another study in which the surgeon used primarily interference screws for fixation on the tibial side, demonstrated the rate of hardware removal at about 5%. 40 Our findings were more like these two studies as compared to the previously cited reoperation studies.…”
Section: Discussionmentioning
confidence: 99%
“…13 The tibial grafts are usually fixed with interference screws 14,15 as they were easy to place, however the tibial interference screws sometimes have complications such as slippage and cysts. [16][17][18][19][20] U-staple is another commonly used fixation device for the tibial tunnel, but it has a significant increase in the risk of symptomatic hardware causing pain on kneeling. 14 The all-inside technique has also been widely introduced for ACL reconstruction with an adjustable-loop button for tibial side fixation, but there is still controversy regarding undesired lengthening of adjustable-loop devices.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true for the tibial graft fixation, which has been considered the weakest link of the reconstruction 12 due to the lower density of the tibial bone and the parallel graft‐fixation associated with the tunnel 13 . The tibial grafts are usually fixed with interference screws 14,15 as they were easy to place, however the tibial interference screws sometimes have complications such as slippage and cysts 16–20 . U‐staple is another commonly used fixation device for the tibial tunnel, but it has a significant increase in the risk of symptomatic hardware causing pain on kneeling 14 .…”
Section: Introductionmentioning
confidence: 99%